Evaluation to the level of some inflammatory markers in hypothyroid insulin resistant patients - Baghdad Science Journal (مجلة بغداد للعلوم)
Hypothyroidism is a condition in which thyroid hormones levels decreased in the blood. These hormones are necessary for energy production and body viability. In many occasions this condition is accompanied or followed by different metabolic disorders. The current study is conducted in the "Specialized center for endocrinology and diabetes" and carried on 70 hypothyroid patients and 60 randomly chosen individuals with normal thyroid function .Both groups were submitted to laboratory tests to evaluate thyroid function (T3,T4.TSH). The study involved evaluation of the relationship between hypothyroidism and insulin resistance (IR) . Health problem related to many diseases , became common lately. Insulin resistance diagnosed through two important tests: C-peptide (CP) and oral glucose tolerance test (OGTT). Patients are considered to have definite insulin resistance (DIR), if they have impaired glucose tolerance (IGT) and high level of CP. If one of the tests is abnormal, the patients have possible insulin resistance (PIR). The current study show that both conditions (hypothyroidism and insulin resistance) are associated and common in women, old and overweight individuals. The results show a significant (P